Effect of Shearing on Thermo-Physiological, Behavior, and Productivity Traits of Two Indonesian Local Sheep Breeds - Panjono; Ibrahim, A.; Ngadiyono, N.; Maulana, H.; Atmoko, B. A. (Tropical Animal Science Journal, 2024)
Thin-tailed sheep (TTS) and Fat-tailed sheep (FTS) are local Indonesian sheep breeds characterized by coarse wool. This study aimed to investigate the effects of wool shearing on the thermo-physiological, behavior, and productivity traits of these sheep. Sixteen selected rams were utilized in this study. Animals were assigned to a factorial completely randomized design and divided into two groups (TTS and FTS) and two treatments (sheared and unsheared). The study spanned three months under controlled conditions. Variables observed included environmental conditions, thermo-physiological parameters (respiratory rate/RR, pulse rate/PR, rectal temperature/RT, and heat stress index/HSI), sheep behavior (feeding duration, drinking frequency, rumination duration, urination frequency, defecation frequency, standing duration, and lying duration), and sheep productivity (feed intake, average daily gain/ADG, and feed conversion ratio/FCR). Data were analyzed using two-way ANOVA. Throughout the study, average temperature and humidity ranged from 25.13-30.48 oC and 64.50%-91.67%, respectively. Wool shearing significantly influenced (p